Sublingual immunotherapy with a five-grass pollen tablet in adult patients with allergic rhinitis: an open, prospective, noninterventional, multicenter study - Pfaar, Oliver (BioMed research international, 2015)
Background. Although the safety and efficacy of sublingual immunotherapy (SLIT) with a five-grass pollen tablet have been demonstrated in randomized clinical trials (RCTs), these outcomes must always be evaluated in real-life medical practice. Methods. In a prospective, open-label, noninterventional, “real-life” study in Germany, we evaluated the safety, tolerability, and effectiveness of SLIT with a five-grass pollen tablet in adults with grass-pollen-induced allergic rhinoconjunctivitis. Results. 808 adults were enrolled between September 2008 and December 2009. 35.3% of the participants experienced at least one adverse drug reaction (ADR), the most common of which were mild-to-moderate gastrointestinal and respiratory disorders. Serious ADRs considered causally related to SLIT treatment occurred in four patients. Overall, the five-grass pollen tablet was considered to have good or very good tolerability by most investigators and patients. Treatment was associated with the relief of nasal, ocular, and bronchial symptoms and decreased symptomatic medication use. However, interpretation of clinical improvements was limited by lower atmospheric grass pollen levels during the study season (relative to the preceding season). Conclusions. In a large population of patients treated in real-life medical practice, SLIT with a five-grass pollen tablet was safe and well tolerated. The patient-reported symptom relief suggests that SLIT was associated with clinical benefits.